Differentiation strategies for the wine and nursery sector: empirical evidence from an Italy region - Piermichele La Sala; Raffaele Silvestri; Francesco Contò (Agricultural and Food Economics, 2017)
The aim of the paper is to analyze how the dynamic capabilities of the wine industry actors, involved in searching for biodiversity, influence and are influenced by the dyadic buyer-supplier relationship. In particular, the study aims at analyzing how the organizational culture, the strategic and relational approach, adopted in the customer-supplier interactions, affect the inter-organizational learning and the value-creating process. For this purpose, an explorative study has been carried out in the wine supply chain of Basilicata region (in southern Italy). Data are collected by submitting a semi-structured interview to the complete population of wineries and grape growers in the abovementioned area. By means of Principal Component Analysis and a Spearman's rank correlation analysis, the paper investigates if the relational approach adopted by the winery toward the grape grower affects positively the dynamic capabilities for wine differentiation strategies. Results show the grape grower are positively influenced by an organizational culture of winemakers based on flexibility and not standardized transformation processes then facilitating the planting choices and assuring the health of cuttings.
Keywords: 330; Dynamic capabilities; Customer value; Wine supply network; Buyer-supplier relationship; Inter-firm learning